Observer reactions to emotional victims of serious crimes: stereotypes and expectancy violations. Issue 9 (21st October 2018) - Bosma, Alice K.; Mulder, Eva; Pemberton, Antony; Vingerhoets, Ad J. J. M.
ABSTRACT: Negative observer reactions towards victims may be related to people's expectations of the characteristics and demeanor of an ideal victim. We examined how expressed emotion, victim sex, and type of victimization influence observers' perceptions of victim credibility, victim character, and harm. Our hypothesis was that angry victims, male victims, and victims of sexual violence are perceived less positively than sad victims, female victims, and victims of physical violence. Additionally, we anticipated that expectancy violations following expressed agentic/high status, or passive/low-status emotions of the victim would lead to negative reactions. Participants ( N  = 335) read a written victim impact statement, by a male or female victim of a sexual or physical assault, in which anger or sadness was expressed. The results show that observers generally respond more negatively to male victims than to female victims, and to victims expressing anger rather than sadness. However, a two-way interaction between expressed emotion and type of crime revealed that expressed emotion only significantly influences character derogation and victim credibility in cases of physical violence. Finally, emotion expectancy violations based on ex-ante expectations lead to derogation and diminished credibility. The discussion focuses on how emotion expectancy violations seem intimately tied to stereotype-ridden features of victimization.